100 km wear-free sliding achieved by microscale superlubric graphite/DLC heterojunctions under ambient conditions. Issue 1 (24th June 2021) - Peng, Deli; Wang, Jin; Jiang, Haiyang; Zhao, Shuji; Wu, Zhanghui; Tian, Kaiwen; Ma, Ming; Zheng, Quanshui
Abstract: Wear-free sliding between two contacted solid surfaces is the ultimate goal in the effort to extend the lifetime of mechanical devices, especially when it comes to inventing new types of micro-electromechanical systems where wear is often a major obstacle. Here we report experimental observations of wear-free sliding for a micrometer-sized graphite flake on a diamond-like-carbon (DLC) surface under ambient conditions with speeds up to 2.5 m/s, and over a distance of 100 km. The coefficient of friction (COF) between the microscale graphite flake, a van der Waals (vdW) layered material and DLC, a non-vdW-layered material, is measured to be of the order of ${10^{ - 3}}$, which belongs to the superlubric regime. Such ultra-low COFs are also demonstrated for a microscale graphite flake sliding on six other kinds of non-vdW-layered materials with sub-nanometer roughness. With a synergistic analysis approach, we reveal the underlying mechanism to be the combination of interfacial vdW interaction, atomic-smooth interfaces and the low normal stiffness of the graphite flake. These features guarantee a persistent full contact of the interface with weak interaction, which contributes to the ultra-low COFs. Together with the extremely high in-plane strength of graphene, wear-free sliding is achieved. Our results broaden the scope of superlubricity and promote its wider application in the future. Abstract : Wear-free sliding for an ultra-long distance of 100 km is achieved by microscale superlubric graphite/DLC heterojunctions under ambient conditions, promising wide application in micro-electromechanical systems, hard drives, bearings etc.